PROFIL TAKSONOMI PENGETAHUAN SISWA SMP DALAMPEMECAHAN MASALAH SOAL CERITA SISTEM PERSAMAAN LINEAR DUA VARIABEL DITINJAU DARI GAYA KOGNITIF - Rahmawati Patta (STKIP Andi Matappa Pangkep, 2018)
The Study aimed at discovering (1) the profile of knowledge taxonomy of student in solving story problem of linear equation system of two variables based on cognitive style, (2) the comparison of knowledge taxonomy of student in solving story problem of linear equation system of two variables based on cognitive style.The Study is a qualitative research. The instrument of the study was the researcher himself as the main instrument guided by tasks in solving story problem of linear equation system of two variables and a valid, reliable guided interview. Data were collected by conducting task based interview. The subjects of the study were two grade VIII students of SMPN 5 Marioriwawo in Soppeng district consisted of one student who categorized as field independent named as SFI (subject field independent) and one student who categorized as field dependent named as SFD (subject field dependent).